Knowledge on Cervical Cancer Prevention and Attitude towards Pap smear and HPV Vaccination among Women Attending a Health Clinic in IPOH, Malaysia - Sandheep Sugathan (Journal of Global Pharma Technology, 2019)
Objectives: Cervical cancer is the second most common cancer among women in Malaysia and is one of the leading causes of cancer mortality in women worldwide. This study was carried out to study the knowledge level regarding cervical cancer prevention and attitude towards Pap smear and HPV vaccination among women attending Greentown outpatient clinic in Ipoh, Malaysia. Methods: Data were collected using a structured questionnaire which included socio-demographic characteristics, knowledge of cervical cancer, Pap smear and HPV vaccination and attitude towards Pap smear and HPV vaccination from a sample of 100 women of age between 16 and 65 years, who were attending the Greentown outpatient clinic in Ipoh, Perak from 21st July to 8th August 2014.Results: Most of the participants were of the age group of 26 to 45 years (44%). Majority of the respondents had good knowledge of cervical cancer, Pap smear and HPV vaccination and showed good attitude towards Pap smear and HPV vaccination. Knowledge levels were significantly different in the different age groups. Attitude on Pap smear and HPV vaccination was significantly higher among higher education groups and employed groups. Conclusion: Age was significantly associated with knowledge levels on cervical cancer prevention and HPV vaccination. Education and occupation levels were significantly influencing the attitude of women regarding cervical cancer, Pap smear and HPV vaccination.